Correlation to Serum Ionized Calcium and Magnesium Concentration with Sympathetic Nerve Functions in Type 2 Diabetes Mellitus (Update Dental College Journal, 2014)
Background : In type 2 DM, a metabolic disorder causes disturbances of different metabolic processes of the body including electrolyte imbalance. Therefore changes in serum level of Ca2+ and Mg2+ may have some relationship to the occurrence of neuropathy. Objective : The study has been designed to observe the sympathetic nerve function status in type 2 diabetic subjects in order to assess the relationship between serum ionized calcium & magnesium. Study design : This cross section study was carried out in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh. Forty seven type 2 diabetic subjects were included in two groups. Group B consisted of 25 recently diagnosed diabetic subjects aged 40-68 years and group C consisted of 22 subjects having duration of diabetes for 10-20 years. Twenty five (25) age and BMI matched healthy subjects were included in group A (non-diabetic) for control. Methods : Sympathetic nerve function were assessed by two simple non-invasive cardiovascular reflex tests. These were systolic blood pressure, response to lying to standing up and diastolic blood pressure response to distain hand grip test. Ionized serum calcium and magnesium were measured by ion sensitive electrode method using NOVA electrode. Data were analyzed by t test, Pearsons correlation co-efficient. Results: Serum ionized calcium levels were significantly higher in both the diabetic group B (P